2020
DOI: 10.1111/den.13693
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 and gastrointestinal endoscopies: Current insights and emergent strategies

Abstract: A new coronavirus emerged in December 2019 in Wuhan city of China, named as the severe acute respiratory syndrome coronavirus‐2 (SARS‐CoV‐2), and the disease was called coronavirus disease‐2019 (COVID‐19). The infection due to this virus spread exponentially throughout China and then spread across >205 nations, including the United States (US). Gastrointestinal (GI) endoscopies are routinely performed in the US and globally. Previous reports of isolated infection outbreaks were reported with endoscopes acting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
94
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 86 publications
(99 citation statements)
references
References 46 publications
0
94
0
5
Order By: Relevance
“…However, there was no clear evidence of transmission directly related to endoscopic procedures in COVID-19-positive patients. Furthermore, it is important to emphasize that no nosocomial outbreaks due to endoscopic procedures were reported and no cases of endoscope-related COVID-19 infection have been reported so far, indicating that current endoscope disinfection techniques are adequate [20].…”
Section: Discussionmentioning
confidence: 99%
“…However, there was no clear evidence of transmission directly related to endoscopic procedures in COVID-19-positive patients. Furthermore, it is important to emphasize that no nosocomial outbreaks due to endoscopic procedures were reported and no cases of endoscope-related COVID-19 infection have been reported so far, indicating that current endoscope disinfection techniques are adequate [20].…”
Section: Discussionmentioning
confidence: 99%
“…Second, a variety of endoscopic procedures including gastroscopy, colonoscopy and endoscopic retrograde cholangio-pancreatography are performed every day, wherein the endoscopists access the GI lumen from a close distance and therefore get exposed to a large number of respiratory, oropharyngeal and gastrointestinal flora. 21,22 Also, many of these procedures are of significantly longer duration, and this further increases the risk of infection to the endoscopist. Johnston et al reported a significant unrecognized exposure to the endoscopist's face of potentially infectious biologic samples during endoscopy.…”
Section: Why Staff In Endoscopy Units Are At High-risk Of Acquiring Cmentioning
confidence: 99%
“…Endoscopists face the tremendous risk of severe acute respiratory syndrome coronavirus‐2 (SARS‐CoV‐2) transmission during endoscopy 1,2 because it may generate respiratory fluid 3 (droplets; 10 1 –10 2 μm, aerosol; <<10 1 μm) 4 . To minimize its transmission risk to the endoscopist, protecting their face from exposure of body fluid is important.…”
Section: Brief Explanationmentioning
confidence: 99%